The underestimated role of major skin commensal Malassezia furfur in the development of neonatal invasive fungal infections - Tatiana V. Priputnevich; Alexey B. Gordeev; Natalia E. Shabanova; Pavel Denisov; Dmitry Yu Trofimov; Ekaterina N. Balashova; Andrey E. Donnikov; Ekaterina L. Yarotskaya; Viktor V. Zubkov; Gennady T. Sukhikh (Heliyon, 2024)
In recent years, some new evidence on the role of Malassezia in late-onset sepsis in immunocompromised patients have been published, but there are still very few studies with special focus on newborns.The prevalence of Malassezia-associated conditions in 3519 newborn patients of general and surgical neonatal intensive care units (NICU) was assessed. All patients underwent pharyngeal and rectal swab screening for Malassezia spp. Identification of Malassezia spp. was carried out with the use of an adapted nutrient media, microscopic assessment of yeast cell morphology, and real-time PCR analysis.Malassezia furfur-induced invasive mycoses (IM) were developed 2.5 times more often in very low birth weight (VLBW) M. furfur-positive newborns, than in neonates with birth weight ≥1500 g, and affecting 15.8 % of VLBW infants. Funguria occurred 16 times more often in VLBW babies, but fungemia incidence was similar for both weight categories. Gastrointestinal (GI) colonization was found in 94.6 % of Malassezia-positive population, and in 8 % of all studied neonates. Among IM patients, death rate was 6.5 %. The specific pathogen was highly detectable by a combination of real-time PCR and an adapted nutrient media. Colonization with M. furfur in newborns was associated with low gestational age, VLBW, and long stay in NICU.The findings emphasize the need to monitor colonization and infection with M. furfur in neonates, staying in ICU for more than two weeks and to improve current diagnostic approaches by using real-time PCR and an adapted nutrient media for M. furfur isolation.